Randomized trial studying metabolic outcomes and quality of life after adrenalectomy versus conservative management for mild autonomous cortisol secretion - Grethe Å Ueland; Oskar Ragnarsson; Anette Heie; Albin Kjellbom; Ola Lindgren; Andreas Muth; Fausto Palazzo; Per L Poulsen; Lars Rolighed; Hrafnkell Baldur Thordarson; Florian Wernig; Anders Bergenfelz (Endocrine Connections)
Objective: Evaluate the impact of adrenalectomy on metabolic parameters and quality of life (QoL) in patients with mild autonomous cortisol secretion (MACS). Method: A multicenter prospective randomized clinical trial compared adrenalectomy with conservative management. Metabolic parameters and QoL were assessed at baseline and after 2 years. Results: Forty-three MACS patients with a single adrenal adenoma were randomized to either adrenalectomy (n = 21) or conservative management (n = 22). At baseline, 33 patients had hypertension, 13 had type 2 diabetes (T2D), 18 used statins, and nine patients had osteoporosis. After 2 years, normalization of cortisol levels post 1 mg dexamethasone suppression test was achieved in 19/21 adrenalectomy patients compared to 2/22 patients in the conservative group (P < 0.01). All adrenalectomy patients had a significant increase in ACTH and DHEA-S. Office blood pressure and daily defined doses of antihypertensives (DDD) improved in nine of 12 adrenalectomy patients versus four of 15 conservatively treated patients (P = 0.01). Using 24 h blood pressure and DDD, improvement rates were five of 11 in the adrenalectomy group and six of 15 in the conservative group (P = 0.78). Among patients without T2D, the 120 min glucose level during oral glucose tolerance test was lower in the adrenalectomy group (6.2 vs 7.3 mmol/L, P = 0.04), but within-group changes were not different (P = 0.76). There were no statistically significant differences in QoL between the two groups. Conclusion: Adrenalectomy showed trends toward improvement in office blood pressure and glucose metabolism in MACS, suggesting possible reduction in cardiovascular risk and metabolic complications.